Transient parkinsonism following mycoplasma pneumoniae infection with normal brain magnetic resonance imaging (MRI) - Tay, C.G.; Fong, C.Y.; Ong, L.C. (SAGE Publications Inc, 2014)
Parkinsonism caused by infection is uncommon in children. We report 2 previously healthy children with acute self-limiting parkinsonism following Mycoplasma pneumoniae infection, with normal brain magnetic resonance imaging (MRI). Our case report expands the phenotype of parkinsonism associated with M pneumoniae infection. We recommend that children with acute parkinsonism preceded by a period of febrile illness, even with a normal brain MRI, should be investigated for M pneumoniae infection.